A polêmica como estratégia persuasiva no discurso da publicidade e propaganda - Azevedo, Diego Gib (2013)
The publicity and propaganda (PP), to create incentives that are redeemed from social contexts, present a socializing speech, becoming regulators instances in a society. Therewith, they can rearrange contextual and existential insights. These pass through by the polemics interactions, that project as arenas for controversies. The persuasive rationality permeates these interactions, the same rationality embedded in advertising and propaganda speeches. Starting from an examination of a typology of polemics a trichotomy consisting of the discussion, dispute and controversy, proposed by Marcelo Dascal this study characterizes the nature polemicist, tracing a relationship with publicity and propaganda. The proposal is to study the use of polemics interactions in this universe of communication, and to interpret how the use of a typology of polemics can be persuasive through symbolic forms that generate the shock, spectacle and sensationalism. A kind of symbiotic relationship that apparently fits and defies the strict logic often applied to PP. A successful improvement capable of glowing to a new consciousness. Given the innovation and personalization have become valued concepts for the contemporary consumer, organizations are changing their communication strategies, adopting new means of expression in order to enchant this "new" consumers increasingly critical, unpredictable, disruptive and information processor, characterized by a lascivious egocentrism. In the current context, organizations must know their consumers, adapt to and surprise them. The ultimate goal is to add value and meaning to the brand. From this perspective, the methodological strategy adopted in this research is the Comprehensive Sociology by Michel Maffesoli, creating opportunity for a critical reading of the daily demarcated in the theories of the imaginary.Through notions and assumptions, the method chosen conveys the idea of transcendence, complication and explanation, opposition and unity. Still, for this study, were chosen three examples of cases: Benetton, Duloren and Atheists and Agnostics Association (ATEA). The corpus examined consists by the advertising of these organizations. So, to answer our concerns, the technique chosen for the analysis of the ads is Semiology, in the theorizing proposed by Roland Barthes. The PP, involved into controversial contents, it contains language and symbols, ambiguity, word games, irony, humor, joy, at long last, denoted and connoted characteristics that may lead to different ways of meaning. The approach chosen corresponds to a requirement of researching the interface of communication with other areas of knowledge, through a transdisciplinary vision that seeks to narrow notions involving, beyond communication, also the administration, marketing, philosophy, psychology, anthropology and sociology